The Macroinvertebrate Community Of The Fast Flowing Rivers In The Crocker Range National Park Sabah, Malaysia. - Mohd Long, Shabdin; Fatimah, Abang; Khairul Adha, A.Rahim (ASEAN Review of Biodiversity and Environmental Conservation (ARBEC), 2002)
The macroinvertebrate community of the fast flowing rivers of the Crocker Range Park examined consists mainly of insects. All the six rivers surveyed demonstrated excellent water quality. The assemblages of taxa reported from the study sites are considered as that typical of the macroinvertebrate fauna in tropical rivers. Out of the existing ten orders of insects that contain aquatic species, a total of 7 orders of aquatic insect species were encountered in the rivers surveyed. These are Ephemeroptera, Odonata, Plecoptera, Hemiptera, Coleoptera, Trichoptera and Diptera. In addition to these insects, the hexapodan Collembola was also encountered. The overall macroinvertebrate density ranges from 71 to 303 individuals per lm sq and all sampling sites were found to sustain at least three groups of taxa with the exception of Sg. Tikolud, which only contains the dipteran chironomids. The dipteran chironomid fauna was dominant and found at all stations and forms the highest density of up to 250 individuals per m2 in Sg. Tandulu and Balayo.